2017
DOI: 10.1097/md.0000000000006134
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hepatic parenchyma lithotomy of hepatolithiasis

Abstract: To investigate the clinical significance of hepatic parenchyma incision by lithotomy near the second hepatic portal area for the treatment of complex hepatolithiasis.A retrospective study was conducted with 35 patients who had complicated hepatolithiasis in our hospital from January 2008 to December 2013, who underwent hepatic parenchyma incision by lithotomy near the second hepatic portal area. The perioperative and long-term outcomes included the stone clearance rate, operative morbidity and mortality, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Our previous study found that IHBD exploration lithotomy for complex IHBD stones achieved satisfactory results [4]. To this end, this study used IHBDIL combined with partial hepatectomy for the treatment of complicated bilateral hepatolithiasis to further assess the safety and efficacy of this treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that IHBD exploration lithotomy for complex IHBD stones achieved satisfactory results [4]. To this end, this study used IHBDIL combined with partial hepatectomy for the treatment of complicated bilateral hepatolithiasis to further assess the safety and efficacy of this treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…SABC dilution 100x. (10) Remove the slide from the incubator and wash it in PBS for 3 times, each time 5 mins, dry the PBS around the tissue and add a chromogenic agent. (11) After rinsing the colored slides with clean water for a period of time, soak them in hematoxylin and dye them.…”
Section: Immunohistochemical Proceduresmentioning
confidence: 99%
“…Combined with intraoperative ultrasound to accurately locate bile duct lesions and the extent of stones, the focus can be effectively removed, and the stone clearance rate is up to 95%. However, the postoperative recurrence rate is still as high as 3% to 15% [8][9][10] . The main reason is that (1) improper application of operation.…”
Section: Introductionmentioning
confidence: 99%